Do China-Financed Dams in Sub-Saharan Africa Improve the Region's Social Welfare? A Case Study of the Impacts of Ghana's Bui Dam - Keyi Tang; Yingjiao Shen (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
This empirical case study by Keyi Tang and Yingjiao Shen conducts an impact evaluation of Ghana's Bui Dam, a China-financed hydropower project completed in 2013. Through two difference-in-differences econometric models and an extensive literature review on relevant field research, this papers analyzes the environmental and socio-economic impacts of the Bui Dam on local households and communities. The authors' empirical models show that the Bui Dam has significantly improved local urban households' access to electricity and increased their ownership of some electric appliances.
Keywords: 330